Uncertainties, resources, and supplier selection in an emerging economy - Xie, E.; Peng, Mike; Zhao, W. (Springer New York LLC, 2013)
Focusing on supplier selection, this article addresses two questions: (1) What are the antecedents that lead to the adoption of various types of selection strategies? (2) What impact do these strategies have on supplier performance? We build a research model showing how both the uncertainty-based and resource-based views drive market-focused and relationship-focused supply selection strategies. Further, we argue that market-focused and relationship-focused selection strategies may have different effects on supplier performance. Specifically, market-focused selection has a positive influence, whereas relationship-focused selection has an inverted U-shaped effect on supplier performance. In addition, the interaction between these two strategies exerts a significant positive influence on supplier performance. Survey data collected from 208 Chinese manufacturers are used to test our hypotheses.